E-Modul Interaktif Teori Bilangan Menggunakan Aplikasi Kvisoft Flipbook Maker - Dodik Mulyono; As Elly (University of Muhammadiyah Malang, 2023)
This study aims to produce an interactive number theory e-module using the Kvisoft flipbook maker application for STKIP PGRI Lubuklinggau students that is valid, practical and effective. The type of research conducted is research and development. The research stages of the interactive number theory e-module using the Kvisoft flipbook maker application were adapted from the Alessi & Trollip development model, which consisted of 4 stages of development, namely: (1) planning; (2) designs; and (3) development. And there are three attributes in it, namely (1) standards; (2) ongoing evaluation; and (3) project management. This research was conducted at STKIP PGRI Lubuklinggau. Based on the data analysis, the validity test produces an interactive number theory e-module using the Kvisoft flipbook maker application which is very valid with an average score of 4.71 and the practicality test produces an interactive number theory e-module using the very practical Kvisoft flipbook maker application with an average score of an average of 4.47 and effective seen from the average score of 74,6 learning outcomes.